Make an Arabic Language Quiz Using The Kahoot Application - Sirojudin, Ahmad; Ma'arif, Syamsul; Shalihah, Siti; Uyuni, Yuyun Rohmatul (Al-Muyassar: Journal of Arabic Education, 2024)
The Kahoot application is a game-based learning platform that is used as educational technology in schools and other educational institutions. The platform allows users, including students and teachers, to create and take interactive learning quizzes called "Kahoots". Kahoot is a multiple choice quiz that can be accessed via a web browser or the Kahoot app. With Kahoot, users can create fun and interactive learning experiences.This research uses a qualitative research approach where qualitative research as a scientific method is often used and carried out by a group of researchers in the field of social sciences, including educational sciences. A number of reasons were also put forward, the essence of which is that qualitative research enriches the results of quantitative research. Qualitative research is carried out to build knowledge through understanding and discovery.Kahoot allows you to create interactive quizzes that can help participants learn Arabic in a fun and interesting way, and Arabic Quiz can be used as a tool to test participants' understanding of the material that has been taught, thereby helping identify areas that need improvement. To reduce the negative impact of using technology, there are also fights between students in the world of education. This can support the learning process by utilizing technological sophistication. This advantage is not only found in the speed factor of obtaining information but also in facilities that can make learning more interesting, such as visuals and interactiveKeywords: kahoot, Arabic lamguage, and education.